Level Abstraksi Reflektif Mahasiswa dalam Menyelesaikan Masalah Teori Bayes - Nurrahmah, Arfatin; Suryana, Andri; Nurfitriyanti, Maya (Institut Agama Islam Negeri Curup, 2024)
This study aims to analyze the level of reflective abstraction of prospective teacher students in solving Bayes' theorem problems in the opportunity theory course. Using a qualitative approach, this research data was taken from prospective 5th semester mathematics teachers, as many as 56 students. The subjects of the study were then selected 5 subjects using purposive sampling techniques. The instruments used are problem-solving tests and interview guidelines have been validated by experts. Documentation data in the form of written test results, videos when doing test questions, and videos during interviews. Qualitative analysis is carried out by data reduction, data presentation, data interpretation, and conclusions. The validity test of the data in this study used triangulation of data collected through various sources, namely comparing the results of student answers and in-depth interviews. The results of this study show that there are differences in the level of skill or capacity of students in solving problems regarding Bayes' proposition. This difference was observed based on the way students thought when given a problem in the form of a story problem.